Analisis Kemampuan Multirepresentasi dalam Menyelesaikan Soal Fisika - Anggereni, Santih; Rudianto, Ahmad; Rafiqah; Ashar, Hasbullahair (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
The purpose of this study was to describe students' ability to represent multiple aspects in answering physics problems and to identify the factors that inhibit and support this ability. This study used a mixed-method approach with an explanatory design. The study was conducted in the Department of Physics Education. The research subjects were selected purposively. The average multirepresentation ability of Physics Education students in solving physics problems was in the low category. Supporting factors included students always completing assigned tasks, seeking help from friends and family when encountering complex issues, and having complete notes and physics e-books. Meanwhile, the inhibiting factors include students rarely practicing solving problems outside class hours, confusion in determining formulas, difficulty with calculations, and a tendency to give up easily when solving problems.